Influence of Maturation Status on Eccentric Exercise-Induced Muscle Damage and the Repeated Bout Effect in Females - Lin, Ming-Ju; Nosaka, Kazunori; Ho, Chih-Chiao; Chen, Hsin-Lian; Tseng, Kuo-Wei; Ratel, Sébastien; Chen, Trevor Chung-Ching (Frontiers in Physiology, 2018)
This study compared changes in indirect muscle damage markers, proprioception and arterial stiffness after elbow flexor eccentric exercise between pre-pubescent (9-10 y), pubescent (14-15 y) and post-pubescent (20-24 y) healthy, untrained females (n=13/group). The maturation of the participants was confirmed by the hand bone age. All participants performed two bouts of 30 sub-maximal eccentric contractions (EC1, EC2) using a dumbbell set at 60% of pre-exercise maximal voluntary isometric elbow flexion strength at 90°. Changes in maximal voluntary concentric contraction (MVC) torque, muscle soreness (SOR), plasma creatine kinase activity, proprioception (position sense, joint reaction angle) and arterial stiffness (carotid-femoral pulse-wave velocity: cfPWV) before to 5 days after EC1 and EC2 were compared among groups by a mixed-design two-way ANOVA. Pre-exercise MVC torque and cfPWV were smaller (P<0.05) for the pre-pubescent (MVC: 10.0 ± 0.9 Nm, cfPWV: 903 ± 60 cm/s) and the pubescent (14.3 ± 1.1 Nm, 967 ± 61 cm/s) than the post-pubescent (19.1 ± 1.4 Nm, 1,103 ± 73 cm/s). Changes in all variables after EC1 were smaller (P<0.05) for the pre-pubescent (e.g., MVC at 1 d post-exercise: -10 ± 6%, peak SOR: 5 ± 2 mm) than the pubescent (-15 ± 9%, 12 ± 6 mm) and the post-pubescent (-25 ± 7%, 19 ± 13 mm). After EC2, changes in all variables were smaller (P<0.05) than those after EC1 for all groups (e.g., MVC at 1 d post-exercise, pre-pubescent: -4 ± 6%, pubescent: -9 ± 4%, post-pubescent: -14 ± 5%; peak SOR: 3 ± 2 mm, 7 ± 3 mm, 11 ± 6 mm), but the magnitude of the repeated bout effect was not different (P>0.05) among the groups. These results show that the extent of muscle damage, and proprioception and arterial stiffness changes after eccentric exercise are greater at later stages of maturation, but the repeated bout effect is not affected by maturation.